Surface Structure and Catalytic Performance of Ni-Fe Catalyst for Low-Temperature CO Hydrogenation. (24th March 2014) - Meng, Fanhui; Zhong, Pengzhan; Li, Zhong; Cui, Xiaoxi; Zheng, Huayan
Abstract : Catalysts 16Nix Fe/Al2 O3 (x is 0, 1, 2, 4, 6, 8) were prepared by incipient wetness impregnation method and the catalytic performance for the production of synthetic natural gas (SNG) from CO hydrogenation in slurry-bed reactor were studied. The catalysts were characterized by BET, XRD, UV-Vis DRS, H2 -TPR, CO-TPD, and XPS, and the results showed that the introduction of iron improved the dispersion of Ni species, weakened the interaction between Ni species and support and decreased the reduction temperature and that catalyst formed Ni-Fe alloy when the content of iron exceeded 2%. Experimental results revealed that the addition of iron to the catalyst can effectively improve the catalytic performance of low-temperature CO methanation. Catalyst 16Ni4Fe/Al2 O3 with the iron content of 4% exhibited the best catalytic performance, the conversion of CO and the yield of CH4 reached 97.2% and 84.9%, respectively, and the high catalytic performance of Ni-Fe catalyst was related to the property of formed Ni-Fe alloy. Further increase of iron content led to enhancing the water gas shift reaction.